(untitled) (Indus Journal of Bioscience Research, 2025)
Objective: to determine frequency of depression and anxiety after primary percutaneous coronary intervention among patients with acute mayocardial infarction using Hamilton rating scale. Methods: This cross-sectional study was performed in outpatients’ clinics of interventional cardiology in National Institute of Cardiovascular Diseases, Karachi, Pakistan from 1st January 2024 to 30th July 2024. The study enrolled patients underwent primary percutaneous coronary intervention within our hospital premises. Anxiety and depression were evaluated based on Rating Scale for Anxiety will be used to evaluate depression (HAMA-14) and Hamilton Rating Scale for Depression (HAMD-17) respectively. Data was analyzed using SPSS version 27. Results: A total of 300 patients were studied with with mean age of 56.4 ± 11.4 years. age range of patients was 28-90 years. About two-third patients were males (64%). About half were belonging to urban area (51%). majority of them had comorbidity of hypertension (88.7%) and diabetes (53.7%). Depression was seen in approximately one-third patients (33.7%) whereas anxiety was found in nearly one-fifth of patients (20.7%). Conclusion: The present study found that burden of depression and anxiety was higher substantial after PCI in MI patients. Integration of mental health assessment and treatment among patients with CAD as soon as after PCI is recommended for optimal and effective treatment.